Front Cover: Intense Molar Circular Dichroism in Fully Conjugated All‐Carbon Macrocyclic 1, 3‐Butadiyne Linked pseudo‐meta [2.2]Paracyclophanes (Chem. Eur. J. 53/2022). Issue 53 (12th September 2022) - Sidler, Eric; Zwick, Patrick; Kress, Charlotte; Reznikova, Ksenia; Fuhr, Olaf; Fenske, Dieter; Mayor, Marcel
Abstract : Unprecedented high molar circular dichroism values for all‐carbon macrocycles were revealed in 1, 3‐butadiyne bridged pseudo‐ meta‐ [2.2]paracyclophanes. The angle and flexibility of the pseudo‐ meta substituents enabled high yielding macrocyclization reactions, and the studied trimeric, tetrameric, pentameric and hexameric structures further displayed astonishing through‐space polymer‐like conjugation lengths. More information can be found in the Research Article by M. Mayor et al. (DOI: 10.1002/chem.202201764 ).